IMPORT SUBSTITUTION AS A BASIC DEVELOPMENT TOOL OF THE RUSSIAN ECONOMY - T. A. Alyokhina; N. V. Zakharkina (Вестник Дагестанского государственного технического университета: Технические науки, 2018)
Objectives The article is devoted to a highly topical issue, the solution of which will allow the existing toolkit for evaluating the import substitution programme in Russia to be improved. The aim of the study was to analyse the practice of applying aspects of import substitution at the regional and country level, as well as to define the objectives and expected results by 2020. The subject of the study consisted in the potentialities and limitations of implementing the import substitution policy as a means of stabilising the economy. The main problems of import substitution in all sectors of the country's economy were identified, conclusions drawn up and proposals developed to address these problems.Methods When writing the article, general scientific cognitive approaches were used in conjunction with experimental and theoretical methods to define goals, problems and expected results of import substitution policies and methods for their achievement, as well as to highlight the most important tools for supporting import substitution projects.Results The detailed results of the research are made available for supporting the implementation of the import substitution policy in the most promising sectors of the economy. The scientific novelty of the research consists in the formulation, theoretical substantiation and resolution of a set of issues related to the systematisation of existing instruments for supporting the policy of import substitution as well as with the problems of the choice of methodological tools and adaptation to Russian realities. The recommendations on the importance of import substitution contained in the article, which are characterised by various examples adapted to Russian conditions, may be of practical interest to the economy of all regions as well as the country as a whole.Conclusion The developed provisions can be used in the formation and implementation of an effective import substitution policy, taking into account all the specifics and problems of implementation.